Gambaran Well Being Lansia yang Aktif Berkegiatan di Komunitas Gereja - Maria Theresia Arie Lilyana; Anindya Arum Cempaka; Maria Manungkalit; Ermalynda Sukmawati (Universitas Malahayati Lampung, 2025)
ABSTRACT Elderly people will experience several biopsychosocial changes. These changes not only affect him physically, but also affect his mental condition. The environment or community has an influence on achieving wellbeing for the elderly to accomodate of self-actualization. Aim of this research to descript of wellbeing in elderly people who are active in church communities. This research mthod used is decriptive analytical. The research was carried out from February to June 2023 with research respondents being elderly people who actively participated in Church elderly activities. The number of respondents in the study was 48 elderly people. The research sample was taken using purposive sampling. The measuring tool used is the Ryff Psychological Wellbeing Scale (PWB). Data processing on wellbeing and wellbeing dimensions uses mean values. The results showed that 24 (50%) respondents had good wellbeing and 24 (50%) had low wellbeing. Based on the result of this research, the picture of the well-being of elderly people who are active in church communities is influenced by the domains of self-acceptance, environment and relationships. The lowest domain in this research is life goals because elderly people feel that when they get older they no longer have any bigger life goals they want to achieve. Elderly people who are active in activities in the church community feel prosperous because they feel accepted, feel like they are part of the community and are able to control their activity environment. Keywords: Activities, Community, Elderly, Well Being. ABSTRAK Lanjut usia akan mengalami beberapa perubahan secara biopsikososial. Perubahan tersebut tidak hanya memengaruhi secara fisik saja, namun juga memengaruhi kondisi kejiwaannya. Lingkungan atau komunitas memiliki pengaruh pencapaian wellbeing bagi lansia sebagai sarana aktualisasi diri. Penelitian ini memiliki tujuan untuk mengetahui gambaran wellbeing pada lanjut usia yang aktif berkegiatan di komunitas gereja. Metode penelitian yang dipergunakan adalah deskriptif analitik. Penelitian dilaksanakan pada bulan Februari hingga Juni 2023 dengan responden penelitian adalah lansia yang aktif mengikuti kegiatan lansia Gereja. Jumlah responden dalam penelitian sebanyak 48 orang lanjut usia. Pengambilan sampel penelitian menggunakan purposive sampling. Alat ukur yang digunakan adalah Ryff Psychological Wellbeing Scale (PWB). Pengolahan data wellbeing dan dimensi wellbeing menggunakan nilai mean. Hasil penelitian menunjukkan 24 (50%) responden memiliki wellbeing yang baik dan 24 (50%) wellbeing rendah. Berdasar hasil penelitian ini gambaran wellbeing lansia yang aktif berkegiatan di komunitas gereja dipengaruhi oleh domain penerimaan diri, lingkungan dan relasi. Domain terendah yang memengaruhi wellbeng adalah tujuan hidup karena lansia merasa saat usia lanjut tidak ada lagi tujuan hidup lebih besar yang ingin dicapai. Lansia yang aktif dalam kegiatan di komunitas gereja merasakan sejahtera karena merasa diri diterima di komunitas tersebut, merasakan menjadi bagian dalam komunitas dan mampu mengontrol lingkungan beraktivitas. Kata Kunci: Kegiatan, Komunitas, Lanjut Usia, Well Being.